Attributing minds to vampires in Richard Matheson’s I Am Legend - Nuttall, Louise (SAGE Publications, 2015)
For Palmer (2004, 2010), and other proponents of a cognitive narratology, research into real-world minds in the cognitive sciences provides insights into readers’ experiences of fictional minds. In this article, I explore the application of such research to the minds constructed for the vampire characters in Richard Matheson’s (1954) science fiction/horror novel I Am Legend. I draw upon empirical research into ‘mind attribution’ in social psychology, and apply Cognitive Grammar (Langacker, 2008), and its notion of ‘construal’, as a framework for the application of such findings to narrative. In my analysis, I suggest that readers’ attribution of mental-states to the vampires in Matheson’s novel is strategically limited through a number of choices in their linguistic construal. Drawing on online reader responses to the novel, I argue that readers’ understanding of these other minds plays an important role in their empathetic experience and their ethical judgement of the novel’s main character and focaliser, Robert Neville. Finally, I suggest that the limited mind attribution for the vampires invited through their construal contributes to the presentation of a ‘mind style’ (Fowler, 1977) for this character.